Odpowiedzi

2010-01-15T20:28:20+01:00
A)58² = (50 + 8)^2 = 50^5 + 2*50*8 + 8^2 = 2500 + 800 + 64 = 3364

-101² = -(100 + 1)^2 = -(100^2 + 2*100*1 + 1^2) = -(10 000 + 200 + 1) = -10 201

-202² = - (200 + 2)^2 = -(200^2 + 2*200*2 + 2^2) = -(40 000 + 800 + 4) = -40 804

b) 45² = (40 + 5)^2 = 40^2 + 2*40*5 + 5^2 = 1600 + 400 + 25 = 2025

-35² = -(30 + 5)^2 = -(30^2 + 2*30*5 + 5^2) = -(900 + 300 + 25) = -1225

72² = (70 + 2)^2 = 70^2 + 2*70*2 + 2^2 = 4900 + 280 + 4 = 5184

-62² = -(60 + 2)^2 = -(60^2 + 2*60*2 + 2^2) = -(3600 + 240 + 4) = -3844

225² = (200 + 25)^ = 200^2 + 2*200*25 + 25^2 = 40 000 + 10 000 + (20 + 5)^2 =
= 50 000 + 20^2 + 2*20*5 + 5^2 = 50 000 + 400 + 200 + 25 = 50 625

-25² = -(20 + 5)^2 = -(20^2 + 2*20*5 + 5^2) = -(400 + 200 + 25) = -625
2 5 2